Direct integration methods versus modal superposition method, on predicting staircases vibrations - Andrade, Pedro (2022)
The majority of Finite Element software’s present two different solutions methods to perform time history analysis of the equations of motion due to dynamic (time-varying) loads: Direct Integration and Modal Superposition. This paper aims to assess which method should be employed in the design of modern flexible staircases, to more efficiently predict human induced vibrations. This was verified by estimating vibrations on a real staircase using the two time domain analysis methods and, then, comparing with vibrations experimentally measured. The results indicate that Direct Integration could yield to overestimated responses due to the limited capacity, as the vibration modes increase, of FE numerical models to realistic predict natural frequencies and modal shapes of a real structure. Therefore, Modal Superposition is suggested to be used for design routines, excluding, for the same reason, the vibration modes with higher frequency content. © 2020 The Authors. Published by ELSEVIER B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0) Peer-review under responsibility of the European Structural Integrity Society (ESIS) ExCo Keywords: Modal Superposition; Direct Integration; Duhamel Integral; Human Walking Vibrations; Flexible Staircases. * Corresponding author. Tel.: +351 291 705 197. E-mail address: jmmns@fe.up.pt Available online at www.sciencedirect.com ScienceDirect Structural Integrity Procedia 00 (2019) 000–000 www.elsevier.com/locate/procedia 2452-3216 © 2020 The Authors. Published by ELSEVIER B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0) Peer-review under responsibility of the European Structural Integrity Society (ESIS) ExCo 1st Virtual European Conference on Fracture Direct Integration Methods versus Modal Superposition Method, on Predicting Staircases Vibrations Pedro Andradea , José Santosb,c,*, Patrícia Escórciob a University of Madeira, 9020-105 Funchal, Portugal b University of Madeira, Faculty of Exact Sciences and Engineering, Department of Civil Engineering and Geology, 9020-105 Funchal, Portugal c CONSTRUCT-LABEST, Faculty of Engineering (FEUP), University of Porto, Portugal Abstract The majority of Finite Element software’s present two different solutions methods to perform time history analysis of the equations of motion due to dynamic (time-varying) loads: Direct Integration and Modal Superposition. This paper aims to assess which method should be employed in the design of modern flexible staircases, to more efficiently predict human induced vibrations. This was verified by estimating vibrations on a real staircase using the two time domain analysis methods and, then, comparing with vibrations experimentally measured. The results indicate that Direct Integration could yield to overestimated responses due to the limited capacity, as the vibration modes increase, of FE numerical models to realistic predict natural frequencies and modal shapes of a real structure. Therefore, Modal Superposition is suggested to be used for design routines, excluding, for the same reason, the vibration modes with higher frequency content.